The Belt and Road Initiative: Inclusive Globalization and Poverty Reduction. (May 2023) - Della Posta, Pompeo
The Belt and Road Initiative (BRI) aims to increase connectivity between regions and countries that market forces excluded from the previous wave of economic globalization. Foreign direct investment (FDI) can create the conditions for the economic takeoff of least-developed countries (LDCs) and developing countries. Although Chinese FDI has nearly doubled since the launch of the BRI in 2013 compared to 2005–2013, it does not seem to be directed toward BRI member countries more than the non-member countries. One exception is South American BRI member countries, which have significantly increased their FDI inflows from China. This is not the case, however, for West Asian countries, where FDI growth has been lower for BRI countries than for the West Asian countries as a whole, and especially for sub-Saharan BRI countries, for which the amount of FDI has even decreased compared to the 2005–2013 period. The BRI's slow start and the countries' gradual entry may explain the delay in seeing the positive results expected from it reflected in the data.